Microesferas de albumina (BSA) reticulada com N',N'-dimetilacrilamida para aplicação em sistemas de liberação de fármacos e antígenos - Sitta, Danielly Ladeira Anibal (2013)
The proteins represent a class of natural polymers with a great potential for application in nano and microparticles, especially albumin, which is the most abundant protein in the circulatory system of the human body. In this work, bovine serum albumin (BSA), chemically modified with maleic anhydride (MA), was used to form micro particles crosslinked with N',N'-dimethylacrylamide (DMAA) through polymerization/crosslinking reaction in a water-in-oil emulsion. The particle morphology was studied considering the influences of DMAA, the stirring time (15, 30, 60 and 120 minutes) and the amount of polyvinyl alcohol (PVA) (0%, 1% and 2%), partially hydrolyzed. It was observed that the modification of BSA with AM was effective and 15 minutes of stirring were enough to induce polymerization/crosslinking reaction. The particles formed in 15 and 30 minutes of stirring in the presence of PVA were predominantly spherical and more homogeneous as compared to the morphology of the sample without PVA, especially those produced in 15 minutes. For stirring times of 60 and 120 minutes, PVA efficiently contributes to the formation of microspheres, especially those obtained in 60 minutes. Albumin-based polymer particle is a promising alternative for the controlled release of vitamin B12, which is a water-soluble vitamin essential for human beings. The in vitro release profile of vitamin B12 was analyzed using samples of BSA modified with AM and polymerized/crosslinked with DMAA, formed in 15 minutes of stirring time and without PVA. For this condition, the average particle diameter was 0.19 ± 0.05 ?m. The percentage of encapsulation was 79 ± 2%. The diffusional coefficients, which allow describe the release mechanisms, were 0.44, 0.62, 1.00, 1.75 and 0.78 for the buffers at pH 2, 4, 6, 8 and 10, respectively. Another proposed application for particles obtained were as an adjuvant for the mucosal vaccine for Hepatitis B. The encapsulation efficiency of surface antigen of hepatitis B (HBsAg) was 74.2%